Remote Education/Homeschooling During the COVID-19 Pandemic, School Attendance Problems, and School Return–Teachers’ Experiences and Reflections - Havik, Trude; Ingul, Jo Magne (Frontiers in Education, 2022)
According to Norway’s Educational Act (§2-1), all children and youths from age 6 to 16 have a right and an obligation to attend free and inclusive education, and most of them attend public schools. Attending school is important for students’ social and academic development and learning; however, some children do not attend school caused by a myriad of possible reasons. Interventions for students with school attendance problems (SAPs) must be individually adopted for each student based on a careful assessment of the difficulties and strengths of individuals and in the student’s environment. Homeschooling might be one intervention for students with SAPs; however, researchers and stakeholders do not agree that this is an optimal intervention. Schools that were closed from the middle of March 2020 due to the COVID-19 pandemic provided an opportunity to investigate remote education more closely. An explorative study was conducted that analyzed 248 teachers’ in-depth perspectives on how to use and integrate experiences from the period of remote education for students with SAPs when schools reopen. Moreover, teachers’ perspectives on whether school return would be harder or easier for SAP students following remote education were investigated. The teachers’ experiences might be useful when planning school return for students who have been absent for prolonged periods.